2007
DOI: 10.1016/j.icarus.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Tidal heating in Enceladus

Abstract: The heating in Enceladus in an equilibrium resonant configuration with other saturnian satellites can be estimated independently of the physical properties of Enceladus. We find that equilibrium tidal heating cannot account for the heat that is observed to be coming from Enceladus. Equilibrium heating in possible past resonances likewise cannot explain prior resurfacing events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(162 citation statements)
references
References 13 publications
5
156
0
1
Order By: Relevance
“…We have shown that equilibrium tidal heating in Enceladus cannot account for the nonsolar heat emanating from Enceladus (Meyer and Wisdom, 2007): equilibrium tidal heating can account for only 1.1(18000/Q S ) GW of the observed 5.8±1.9 GW (Spencer et al, 2006). Provided the origin of the observed heating is tidal heating, it is possible that Enceladus is oscillating about equilibrium.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…We have shown that equilibrium tidal heating in Enceladus cannot account for the nonsolar heat emanating from Enceladus (Meyer and Wisdom, 2007): equilibrium tidal heating can account for only 1.1(18000/Q S ) GW of the observed 5.8±1.9 GW (Spencer et al, 2006). Provided the origin of the observed heating is tidal heating, it is possible that Enceladus is oscillating about equilibrium.…”
Section: Introductionmentioning
confidence: 83%
“…where m = (L + 4)/3, and β = 13 for Io in the Io-EuropaGanymede resonance and β = 30.69 for Enceladus in the Enceladus-Dione resonance (Meyer and Wisdom, 2007). The equilibrium value of the square of the eccentricity is…”
Section: Ojakangas and Stevenson Evolution Equationsmentioning
confidence: 99%
“…The intensity of the geysers of Enceladus depends on how close or far the satellite is from Saturn [47].…”
Section: Discussion Of Some Detail Related To the Estimation Of The Rmentioning
confidence: 99%
“…The Cassini probe has observed that Enceladus is a currently active body emanating water plumes, possibly implying liquid water in its subsurface (e.g., Porco et al 2006). If Enceladus is in an equilibrium state of the resonance with Dione, the tidal heating rate generated in Enceladus is ∼1.1 GW at Q s = 18 000 (Meyer & Wisdom 2007), which is independent of the interior structure of Enceladus. However, the equilibrium heating rate increases with decreasing Q s (Meyer & Wisdom 2007;Lainey et al 2012), which may affect Enceladus' structure and activity.…”
Section: Introductionmentioning
confidence: 95%